Outgrowing the Predicament? National Identity and Seoul's Dokdo Policy1. (August 2015) - Flamm, Patrick
<x xml:space="preserve">Abstract</x> The Dokdo/Takeshima dispute between the ROK and Japan remains the single biggest obstacle to an improvement of South Korean–Japanese relations. The issue forces South Korean foreign policy actors to constantly maneuver between engagement with Japan out of strategic interests and confrontation because of the islets' symbolic value for Korean national identity. Still, the scholarly debate has failed to comprehensively grasp the constitution of Dokdo as a political issue, while reducing it to "irrational emotions" that unnecessarily hinder urgent bilateral cooperation. Further, there prevails a one‐dimensional and fixed understanding of Korean identity as largely post‐colonial, without acknowledging the recent research on an increasingly internationalized Korean self‐understanding. In taking a constructivist, discourse analytical approach, I am able to provide a sound assessment of the various active identity narratives relevant to Seoul's Dokdo policy, while considering the odds for political change.